Gulf stream moisture fluxes impact atmospheric blocks throughout the Northern Hemisphere - Mathews,JP; Czaja,A; Vitart,F; Roberts,C (Geophysical Research Letters, 2024)
In this study, we explore the impact of oceanic moisture fluxes on atmospheric blocks using the ECMWF IFS. Artificially suppressing surface latent heat flux over the Gulf Stream (GS) region reduces atmospheric blocking frequency across the Northern Hemisphere by up to 30%. Affected blocks show a shorter lifespan (−6%), smaller spatial extent (−10%), and reduced intensity (−0.4%), with an increased number of individual blocking anticyclones (+17%). These findings are robust across various blocking detection thresholds. Analysis reveals a qualitatively consistent response across all resolutions, with Tco639 (∼18 km) showing the largest statistically significant change across all blocking characteristics, although differences between resolutions are not statistically significant. Exploring the broader Rossby wave pattern, we observe that diminished moisture fluxes favor eastward propagation and higher zonal wavenumbers, while air-sea interactions promote stationary and westward-propagating waves with zonal wavenumber 3. This study underscores the critical role of the GS in modulating atmospheric blocking.